Nowa Republika . no. 31, 1989 - Ruch Społeczny "Solidarność", [ed. Jan Kosiński, Marek Woliński] (Wydawnictwo Kret, 1989)
Creation and circulation: Publication with reviews of periodicals and books in underground circulation. From no. 23(1988) publication is part of the Koordynacja Wydawnicza at RKW NSZZ "Solidarność" Region Dolny Śląsk